2004
DOI: 10.1080/10428190412331283279
|View full text |Cite
|
Sign up to set email alerts
|

C-kit Receptor (CD117) Expression on Plasma Cells in Monoclonal Gammopathies

Abstract: The surface expression of CD117 antigen (c-kit) on plasma cells from 158 multiple myeloma (MM), 12 plasma cell leukemia (PCL), 7 MGUS, 7 IgM lymphoplasmacytic lymphoma patients and 10 healthy subjects has been analyzed by flow cytometry using triple staining with the monoclonal antibodies CD138, CD117 and CD38. The antigen expression intensity was calculated as relative fluorescence intensity (RFI) and for direct quantitative analysis the QuantiBRITE test (Becton Dickinson) was applied. Antibody bounding capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 19 publications
1
20
2
Order By: Relevance
“…In most published reports, 20% of cells expressing an antigen of interest is considered the threshold value to define an antigen as ''positive'' or ''negative'' and discriminate if the PCs are normal or neoplastic, while a j/k ratio ranging between 0.5 and 3 defines polyclonal (normal) PCs (13,14,25,(38)(39)(40). Therefore, this traditional method described by literature was also applied to our patient samples to define the normal or abnormal expression for each antigen.…”
Section: Comparison Between Histologic Results and Flow Cytometric Anmentioning
confidence: 99%
See 2 more Smart Citations
“…In most published reports, 20% of cells expressing an antigen of interest is considered the threshold value to define an antigen as ''positive'' or ''negative'' and discriminate if the PCs are normal or neoplastic, while a j/k ratio ranging between 0.5 and 3 defines polyclonal (normal) PCs (13,14,25,(38)(39)(40). Therefore, this traditional method described by literature was also applied to our patient samples to define the normal or abnormal expression for each antigen.…”
Section: Comparison Between Histologic Results and Flow Cytometric Anmentioning
confidence: 99%
“…In most existing reports, 20% of cells expressing an antigen of interest is considered the threshold value to define an antigen as ''positive'' or ''negative'' and discriminate if the PCs are normal or neoplastic (13,14,(38)(39)(40). However, rather than a strict 20% cut-off, Rawstron et al (2) suggested variable levels of expression of CD19, CD56, CD20, CD117, CD28, CD27, CD81, and CD200 on polyclonal PCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subjects of analysis were plasma cells identified on the basis of strong CD38 expression, expression of CD138 and CD45 low/-as well as their typical light scatter distribution. Monoclonality was confirmed by immunoglobulin light chain The intensity of particular antigen expression was measured by an indirect quantification method previously described and the values of this expression intensity were calculated as Relative Fluorescence Intensity (RFI) indices [3]. To determine CD45 expression intensity on plasma cells, we applied a method of referring RFIs on monoclonal plasma cells to RFIs on lymphocytes, and a score of CD45 RFI values on myeloma cells to CD45 RFI values on lymphocytes was calculated in particular patients.…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
“…Besides their immunophenotypic marker function, these antigens contribute relevant processes for cell survival, participate in lytic bone lesion formation, and mediate the action of novel anti-myeloma drugs and resistance to treatment [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%